KONFLIK PERBATASAN LIMA DESA DI WILAYAH KABUPATEN KAMPAR DAN KABUPATEN ROKAN HULU (SEBUAH TINJAUAN HISTORIS DAN DAMPAKNYA TERHADAP PELAYANAN MASYARAKAT) - Shofiyah, Siti Shofiyah Siti; Saiman, Marwoto Saiman Marwoto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The background of this thesis is a regional expansion that causes changes in borders and boundaries are not clearly defined. Giving rise to conflicts between the adjacent areas. The purpose of this study was to determine (1) How the background of the conflict in the Border Region Five Villages in Kampar and Rokan Hulu. (2) To find out how the state government in five rural villages during the conflict in the region Border Scramble Kampar and Rokan Hulu. (3) To determine the impact of the conflict on the community service in various aspects, such as demographic aspects, economic, social, political or security. The method used in scientific writing is the historical method and documentaries. Moreover, I also use a descriptive method that is useful as a complement to obtain the data. The results obtained that historically cause conflicts over territory which occurred in five rural areas arise because Unclear boundaries in the Act governing the Establishment of Local Government, this conflict also makes five rural communities feel confused because the dualism of leadership in local government that is of the District Kampar and also from District Rokan Hulu. And society is harmed by such conflict. As an example in the community election be losing their voting rights, or in the field of population feel confused society must take care of KTP, KK in Kampar government or in Rokan Hulu .Keywords : Border conflicts , Kampar , Rokan Hulu , Impact